2014
DOI: 10.1007/s10948-013-2472-1
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Gap in the (Hg1−x Sn x )Ba2Ca2Cu3O8+y Superconductor

Abstract: The experimental data show that the increase of tin in the (Hg 1−x Sn x )Ba 2 Ca 2 Cu 3 O 8+y superconductor results in a visible increase in the pseudogap temperature (T ) with a slight decrease in the value of the critical temperature (T C ). Based on the above results, the dependence of the average amplitude of the energy gap on the temperature (G(T )) has been determined for x ∈ 0, 0.25 . On this basis, it has been found that the dimensionless ratio R G ≡ G(0)/k B T C increases with the increasing tin cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…At the same time, the determined values of the parameter R G fairly agree with the experimental results [1,13,14].…”
Section: The First Postulate States: In the Superconductivity Domain supporting
confidence: 85%
“…At the same time, the determined values of the parameter R G fairly agree with the experimental results [1,13,14].…”
Section: The First Postulate States: In the Superconductivity Domain supporting
confidence: 85%
“…In particular, it was shown that the model allows to calculate correctly the critical temperature and the energy gap at zero Kelvin. It should be noted that the appropriate calculations were carried out for the large number of the chemical compounds, and each time obtained results were consistent with the experimental data .…”
Section: The Eliashberg Approach the Pseudogap And The Pairing Mechsupporting
confidence: 62%
“…Most researchers emphasize the importance of the strong electron correlations [9]. However, some of them pay attention to the role of the electron-phonon interaction [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%